A generalizable method for the construction of MOF@polymer functional composites through surface-initiated atom transfer radical polymerization. Issue 6 (12th December 2018) - He, Sanfeng; Wang, Hongliang; Zhang, Cuizheng; Zhang, Songwei; Yu, Yi; Lee, Yongjin; Li, Tao
Abstract : A universal method to grow polymers on MOF surfaces with well-defined thickness, sequence and functionality. Abstract : We report a generalizable approach to construct MOF@polymer functional composites through surface-initiated atom transfer radical polymerization (SI-ATRP). Unlike conventional SI-ATRP that requires covalent pre-anchoring of the initiating group on substrate surfaces, in our approach, a rationally designed random copolymer (RCP) macroinitiator first self-assembles on MOF surfaces through inter-chain hydrogen bond crosslinking. Subsequent polymerization in the presence of a crosslinking monomer covalently threads these polymer chains into a robust network, physically confining the MOF particle inside the polymer shell. We demonstrated the universality of this approach by growing various polymers on five MOFs of different metals (Zr, Zn, Co, Al, and Cr) with complete control over shell thickness, functionality and layer sequence while still retaining the inherent porosity of the MOFs. Moreover, the wettability of UiO-66 can be continuously tuned from superhydrophilic to superhydrophobic simply through judicious monomer(s) selection. We also demonstrated that a 7 nm polystyrene shell can effectively shield UiO-66 particles against 1 M H2 SO4 and 1 M NaOH at elevated temperature, enabling their potential application in demanding chemical environments.